Swiss mercenaries in the Dutch East Indies a transimperial history of military labour, 1848-1914 - Krauer, Philipp 1987- (Leiden University Press, 2024)
Between 1848 and 1914 around 5,800 Swiss Mercenaries enlisted in the Dutch Colonial Army (KNIL) to fight in the Dutch East Indies (present-day Indonesia). Following the traces of these mercenaries beyond the confines of the Dutch Empire, this book elucidates the complexities of the nineteenth-century military labour markets and provides an intricate examination of the mercenaries' socio-cultural backgrounds, their motives, and their engagement with local communities and authorities. In doing so, it reveals the profound effects of colonialism not only on the colonies themselves, but also on the social, economic and cultural landscape of the European hinterland
"The open access edition was made possible by a grant from the Swiss National Science Foundation (SNF) for the promotion of scientific research."
Keywords: Geschichte 1848-1914; Imperialismus; Söldner; Schweizer Soldat; Kolonialismus; Niederländisch-Indien; History, Art History, and Archaeology; HIS; Colonial Studies; COLONIAL; Dutch and The Netherlands; DUTCH NL; Colonialism, Military History, Labour & Migration History, History of the Dutch East Indies, History of Switzerland, History of Indonesia; Mercenary troops / Switzerland / History / 19th century; Mercenary troops / Switzerland / History / 20th century; Switzerland / History, Military / 19th century; Switzerland / History, Military / 20th century; Netherlands / Colonies / Defenses / Asia; Netherlands / Colonies / Asia / History / 19th century; Netherlands / Colonies / Asia / History / 20th century; Imperialism / History / 19th century; Imperialism / History / 20th century; Social and cultural history; Colonialism and imperialism; HISTORY / Europe / Western; HISTORY / Military / Other; POLITICAL SCIENCE / Colonialism & Post-Colonialism; Early modern warfare (including gunpowder warfare)